Sustainable development and sustainability as study objects for comparative management theory: Proposing styles of reasoning for an unknown metropole. Issue 2 (5th May 2015) - Borim-de-Souza, Rafael; Balbinot, Zandra; Travis, Eric Ford; Munck, Luciano; Takahashi, Adriana Roseli Wünsch
Abstract : Purpose: – The purpose of this paper is to characterize sustainable development and sustainability as study objects for comparative management theory. Design/methodology/approach: – The primary objective of this paper is to characterize sustainable development and sustainability as study objects for comparative management theory. Findings: – Analytical dimensions were related to establishing three proposals, which represent possible theoretical routes for characterizing sustainable development and sustainability as study objects for comparative management theory. A framework which illustrates the theoretical route taken to develop these proposals is presented at the end of the theoretical-analytical discussions. Research limitations/implications: – This paper considers that discussion about sustainable development, sustainability and comparative management theory, as interesting themes for organizational studies, lack epistemological clarity and theoretical depth. Such shortcomings are identified based upon the difficulty in identifying ontological postures, epistemological perspectives, dominant paradigms and conceptual approaches that enable greater coherence to analysis of these themes, and also support the undertaking of research that can contribute to enriching proposals related to comparative management theory. Originality/value: – This is an innovative paper as it relates comparative management theory approaches with structural concepts from sustainable development and sustainability developed using contributions from organizational theories, sociological reflections, and political science. The proposed characterization is intended to blaze new and alternative epistemological paths for adding greater rigor to empirical research focussed on the relationship investigated here in a theoretical context.